2015
DOI: 10.1377/hlthaff.2015.0548
|View full text |Cite
|
Sign up to set email alerts
|

Insurer Competition In Federally Run Marketplaces Is Associated With Lower Premiums

Abstract: Federal subsidies for health insurance premiums sold through the Marketplaces are tied to the cost of the benchmark plan, the second-lowest-cost silver plan. According to economic theory, the presence of more competitors should lead to lower premiums, implying smaller federal outlays for premium subsidies. The long-term impact of the Affordable Care Act on government spending will depend on the cost of these premium subsidies over time, with insurer participation and the level of competition likely to influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…The magnitude of this effect ranges from 1.9% in 2014 to 2.9% in 2015, across all four specifications. This effect is similar to the range of 1.2-3.5% decline in premiums found in Jacobs et al (2015) and Gabel et al (2015). As the OLS model is likely to suffer from both simultaneity and omitted variable biases, as we describe in Section 1, we do not impose a causal interpretation to the results in Table 2.…”
Section: Are Premiums Correlated With Competition?supporting
confidence: 59%
See 1 more Smart Citation
“…The magnitude of this effect ranges from 1.9% in 2014 to 2.9% in 2015, across all four specifications. This effect is similar to the range of 1.2-3.5% decline in premiums found in Jacobs et al (2015) and Gabel et al (2015). As the OLS model is likely to suffer from both simultaneity and omitted variable biases, as we describe in Section 1, we do not impose a causal interpretation to the results in Table 2.…”
Section: Are Premiums Correlated With Competition?supporting
confidence: 59%
“…In this analysis, they control for the plan year, whether the state had an FFM or ran its own marketplace, plan type, carrier category, whether the area was urban, suburban or rural, market concentration in the individual insurance market prior to the ACA, number of insurers competing in the rating area, median family income, percentage of the uninsured population, and a state identifier. Jacobs et al (2015) expands upon this analysis by removing omitted time-invariant factors with a FD multivariate regression analysis of 2014 and 2015 data from the FFMs. They find that one more insurer is associated with a 1.2% reduction in the 2LPS premium, after controlling for the 2012 US census population estimate, the percentage of population under the age of 18 years and over the age of 64 years, the percentage of rural population, median household income, the percentage of uninsured adults, and the percentage of population with incomes below poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 Studies that have investigated plan affordability in the Marketplaces to date have focused almost exclusively on premiums. 4,[8][9][10][11] The literature has established that increased insurer competition results in lower Marketplace premiums. [2][3][4][5] Insurers operating in counties with multiple competitors have an incentive to lower premium levels because Marketplace consumers are very price sensitive with respect to health plan choice.…”
mentioning
confidence: 99%
“…More broadly, a number of studies have found insurer market concentration to be associated with lower provider prices . However, research is mixed regarding whether these lower prices translate into lower premiums for enrollees . This is important because quality improvement, which has a direct benefit to enrollees similar to reduced premiums, may therefore not improve with improved insurer bargaining power.…”
Section: Relevant Literaturementioning
confidence: 99%
“…[22][23][24] However, research is mixed regarding whether these lower prices translate into lower premiums for enrollees. [25][26][27][28] This is important because quality improvement, which has a direct benefit to enrollees similar to reduced premiums, may therefore not improve with improved insurer bargaining power.…”
Section: Studies From the Mid-2000s By Scanlon Et Al Examine Qualitymentioning
confidence: 99%